Knowledge regarding harmful effects on cell phone use among higher secondary school students Bharatpur Chitwan, Nepal - Gautam, S; Shakya, J (Journal of Chitwan Medical College, 2017)
There is no doubt that the cell phone is a very useful today, cell phones are a major part of society. It eases communication with colleagues, friends and relatives. But every technology that provides such benefits comes with consequences. The effect of cell phones on youth and society is excessive. A descriptive cross-sectional study was used to identify the knowledge regarding harmful effects on cell phone use among higher secondary school students. The study population consisted of 70 higher secondary school students of Saptagandaki Multiple College, Bharatpur10, Chitwan. Non-probability purposive sampling technique was used to select the college and faculty .Whereas, out of 145 students, 70 students were selected respectively by using simple random sampling technique from the lottery method. Data was analyzed by using SPSS and various tests frequency, mean, median, percentage and standard deviation and the findings were presented in tables. Chi-square test as inferential statistics was used to analyze the associations between the independent and dependent variables. The study findings revealed that out of the 70 respondents, 24 (34.3%) respondents were in the age of 17 years and 3 (4.3%) respondents were in age of 15 years. The mean age was 17.31 with standard deviation of 1.04. Similarly regarding the sex 45 (64.3%) were male and 25 (35.7%) were female. Respondents’ have good level of knowledge regarding harmful effects of cell phone as it causes addiction on cell phone 90.0% but have average level of knowledge as it causes headache 78.6%, gradual loss of hearing 77.1%, eye strain 70.0%, dizziness 71.4%, skin allergy 71.45%, risk for breast cancer 75.7% and have poor level of knowledge as it causes dry eye 47.1%, warmness around ear 35.7%, decrease fertility rate 22.9%, tiredness if used after lights out. Out of 70 respondents, 53 (75.7%) of respondents answered risk for breast cancer is the harmful effects of cell phone if kept on chest region, and 20 (28.6%) answered chest injury. The level of knowledge regarding harmful effects on cell phone use is statistically not- significant with age (p=0.141), sex (p=0.943), faculty (p=0.632), grade (p=0.490) and previous experience (p=0.311).The study concluded that the some educational intervention need to lunch by institution in order to enhance the awareness among higher secondary school students.